Improving soil water dynamics and crop productivity through conservation tillage in arid regions - Juan Li; Ziru Niu; Zhen Guo; Jinbin Li; Shenglan Ye; Dongwen Hua (Scientific Reports)
Abstract Exploring the impact of different tillage practices on soil moisture retention and crop yield in dryland winter wheat- spring maize rotation on the Loess Plateau is crucial for enhancing rainfall utilization and advancing tillage systems in arid agricultural regions. A long-term field experiment was conducted from 2019 to 2021 in the Weibei dryland area of the Loess Plateau to investigate the effects of conservation tillage. Continuous tillage (CC) was used as the control, with three alternative methods: no-tillage (NN), subsoiling (SS), and a combination of no-tillage and subsoiling (NS). The study assessed the impact of these tillage practices on soil water retention, bulk density, relative chlorophyll content, crop yield, and water use efficiency during both the fallow period and the growing seasons of winter wheat and spring maize. The results revealed the following: (1) All treatments effectively reduced soil bulk density in the 0–60 cm soil layer relative to pre-experiment levels and increased soil porosity. Among the treatments, NS was the most effective, reducing the average bulk density in the 0–60 cm layer by 0.1–0.2 g cm⁻³ and increasing porosity by 2.0-5.5% compared to the other treatments. (2) During the fallow period, tillage treatments significantly enhanced soil water content and storage compared to CC, with NN and NS treatments showing superior water retention effects. (3) In the winter wheat growing season, the average soil water content in the 0–200 cm layer for the NN, SS, and NS treatments was 4.8%, 5.4%, and 3.5% higher than that of CC, respectively. During the spring maize growing season, the increases were 49.3 mm, 17.7 mm, and 36.3 mm, respectively. All tillage treatments resulted in higher soil water storage in the 0–200 cm layer compared to CC, with NN being the most effective during the winter wheat season and SS during the spring maize season. (4) Compared to CC, all tillage treatments improved SPAD values, with NS showing the most significant effect. (5) All treatments increased the yields of both winter wheat and spring maize compared to the control, with increases of 5.4-10.0% for winter wheat and 7.3-18.7% for spring maize. Notably, NS significantly boosted crop yields. Water use efficiency improved by 1.2-6.0% for winter wheat and 5.5-31.3% for spring maize, with SS improving water use efficiency for winter wheat and NS for spring maize. In conclusion, the combination of no-tillage and subsoiling significantly improves soil quality, crop yield, and water use efficiency in the drylands of the Loess Plateau. This makes it a promising tillage practice for the sustainable development of dryland agriculture.